Tariqa and Prosperity: Investigating Shiddiqiyyah Tariqa Experience in Empowering Communities in Jombang, East Java, Indonesia - Abd. Syakur (KACA (Karunia Cahaya Allah): Jurnal Dialogis Ilmu Ushuluddin, 2023)
This article describes the struggle of the Shiddiqiyyah to become a nationalist tariqa that teaches a balanced way of life. The research was conducted qualitatively. Data was collected by interviewing the murshid, three caliphs, and 20 tariqa followers, observing their activities, and documenting the doctrine and community empowerment activities. The collected data were analyzed using reflective-inductive thinking techniques to produce a systematic narrative about the movements of the Shiddiqiyyah tariqa. The results show that Shiddiqiyyah is a native Indonesian tariqa founded by Muchtar Mu’thi in Jombang, East Java, who struggled the tariqa to become a tariqa teaching the love of the motherland and dhikr of work. To realize this, first, the murshid of Shiddiqiyyah develops the doctrine of ‘unity of faith and humanity’ so that the tariqa adherents become humanity who are close to Allah through dhikr kautsaran and work creativity; second, holding training to cultivate local resources into goods of economic value such as bags, mats, and wallets. [Artikel ini menjelaskan perjuangan tarekat Shiddiqiyyah untuk menjadi tarekat nasionalis yang mengajarkan cara hidup yang seimbang duniawi-ukhrawi. Penelitin dilakukan secara kualitatif. Data dikumpulkan dengan mewawancarai musrsyid, tiga khalifah, dan dua puluh pengikut tarekat; mengamati kegiatan warga tarekat; dan mendokumentasikan doktrin dan kegiatan pemberdayaan masyarakat. Data yang terkumpul dianalisis menggunakan teknik berpikir reflektif-induktif untuk menghasilkan narasi sistematis tentang program-program tarekat Shiddiqiyyah. Hasil penelitian menunjukkan bahwa Shiddiqiyyah merupakan tarekat asli Indonesia yang didirikanoleh Muchtar Mu’thi di Jombang, Jawa Timur, yang memperjuangkan Shiddiqiyyah untuk menjadi tarekat yang mengajarkan cinta tanah air dan dzikir kerja. Untuk mewujudkan hal tersebut maka, pertama, mursyid Shiddiqiyyah mengembangkan doktrin ‘kesatuan iman dan kemanusiaan’ agar penganut tarekat menjadi umat yang dekat dengan Allah melalui dzikir Kausaran dan kerja kreatif; kedua, mengadakan pelatihan untuk mengolah sumberdaya alam berupa daun pandan dan bambu menjadi produk barang bernilai ekonomi seperti tas, tikar, dan dompet.]